Numerical gamification: "Mari Mengenal Nombor" for preschool children / Muhammad Saifullah Khairudin ... [et al.] - Khairudin, Muhammad Saifullah; Ahmad, Samsiah; Zulkifli, Zalikha; Mohamad, Masurah; Abdul Latif, Lily Marlia (2020)
Preschool education is important in learning experience in the world of education. In 21st century, preliminary education especially preschool are able to understand the numbering system as foundation for other mathematical operation. However, some of the children in preschool have difficulties understand the numbers when it involved addition and subtraction. Therefore, in this project had invent learning number in gamification approach technique in order to provide learning numbers among preschool much interesting, entertaining and effective rather than traditional or conventional approach. This game had been developed based on multimedia development life cycle with the adaptation of mechanic, dynamic and aesthetic framework. This numerical gamification has been developed in Malay language which known as "Mari Mengenal Nombor". This project focuses more on preschool children having learning experience through game that has been developed. Thus, this innovation has shown significantly improved among preschool children in learning numbers as adaptation of Digital of Education 5.0.